First Molecular Characterization of Hysterothylacium fabri Larvae (Nematoda: Raphidascarididae) in the Mediterranean Sea Based on the Small Subunit Ribosomal RNA Gene Sequence - Pekmezci, Gökmen Zafer; Şimşek, Emrah; Sürsal, Neslihan; Karademir, Gupse Kübra (Afyon Kocatepe Üniversitesi, 2021)
Hysterothylacium fabri is commonly reported in various Mediterranean fish. However, there is no data on themitochondrial ribosomal RNA (rrnS) gene sequence of H. fabri larvae in the Mediterranean Sea waters. Therefore,we aimed to reveal molecular characterization of H. fabri based on the rrnS gene sequence in the current study.Firstly, the fourth stage of H. fabri larvae were identified at parasitological examination from Mullus barbatus in theMediterranean Sea. Morphologically identified H. fabri larvae herein were also supported by the sequencing of thenuclear ribosomal ITS gene regions. In the next step, the rrnS gene of these larvae was molecularly analysed. OurH. fabri isolate (MK886659) showed 96.42% identity with H. fabri reported from China (MF140349) based on therrnS gene. The nucleotide difference based on the rrnS gene between Chinese isolate (MF140349) and our H. fabriisolate (MK886659) was determined as 3.2%. Consequently, for the first time, the mitochondrial rrnS genesequencing of H. fabri from the Mediterranean waters were performed in the current study.

Hysterothylacium fabri sıklıkla farklı türdeki Akdeniz balıklarında bildirilmektedir. Ancak, Akdeniz sularındaki H. fabri larvasının mitokondriyal ribozomal RNA (rrnS) gen bölgesinin sekansı üzerine herhangi bir veri bulunmamaktadır. Bu yüzden, bu çalışmada, H. fabri’nin rrnS gen bölgesinin sekansına göre moleküler karakterizasyonunu ortaya koymayı amaçladık. İlk olarak, Akdeniz'deki Mullus barbatus'tan dördüncü dönem H. fabri larvaları parazitolojik muayenede teşhis edildi. Burada morfolojik olarak teşhis edilen H. fabri, nükleer ribozomal ITS gen bölgesinin DNA dizi analizi ile de desteklendi. Bir sonraki aşamada ise bu larvaların rrnS geni moleküler olarak analiz edildi. RrnS gen bölgesine göre, H. fabri izolatımız (MK886659) Çin’den rapor edilen H. fabri (MF140349) ile %96,42 oranında benzerlik gösterdi. Çin (MF140349) izolatı ile H. fabri (MK886659) izolatımız arasındaki nükleotid farklılığı ise rrnS genine göre %3,2 olarak belirlendi. Sonuç olarak bu araştırma ile ilk kez Akdeniz sularından H. fabri'nin mitokondriyal rrnS sekanslaması gerçekleştirildi.
Akdeniz’deki hysterothylacium fabri (nematoda: raphidascarididae) larvasının ilk kez küçük alt ünite ribozomal RNA gen bölgesinin sekansına göre moleküler karakterizasyonu
Tam Metin / Full Text
Keywords: Hysterothylacium fabri; Mediterranean Sea; Mitochondrial rrnS Gene; Molecular Characterization; Akdeniz; Hysterothylacium fabri; Mitokondriyal rrnS Gen; Moleküler Karakterizasyon